Nomenclatural notes on Goeppertia (Marantaceae) - Saka, Mariana Naomi; Lombardi, Julio Antonio (Phytotaxa, 2015)
A recent molecular based phylogeny (Borchsenius et al. 2012) redefined the genus Goeppertia Nees (1831: 337) to include all the subgenera of Calathea Meyer (1818: 6) proposed by Schumann (1902) with the exception of C. subgenus Calathea Körnicke (1862: 112). As a result, several species of Calathea recently described were transferred to Goeppertia (Braga 2014). Similarly, a taxonomic revision of the Brazilian species, currently carried out by the first author, led to the conclusion that Calathea polytricha Baker (1894: 497) should be combined in Goeppertia. This species features the synapomorphies of Goeppertia, such as simple inflorescences and corolla lobes straight to spreading, and belongs to Schumann’s subgenus Pseudophrynium Körnicke (1862: 113). During the taxonomic revision, other names have been considered synonyms and are typified here.